“The Sole You Found was the Soul of the Festival”: Archaeological Study of a Rock Festival in Seinäjoki, Finland - Äikäs, Tiina; Perttola, Wesa; Kuokkanen, Tiina (Journal of Contemporary Archaeology, 2016)
In 2010, we carried out archaeological fieldwork during a rock festival in Seinäjoki, Finland. We had two aims: first, to investigate what material culture tells about how people experience the place where a rock festival is held and second, to popularize archaeology. Our methods included test pits, mapping garbage with RTK-GPS and interviews. This article addresses the questions of transience, temporality and place attachment as witnessed by archaeological finds from a festival. Our results emphasize both the long- and short-term changes in the function of this place. In addition, the material culture reveals traces of people’s behaviour that were too mundane to be remembered. It also shows that the places which people choose for their actions are not always those selected by the organizers. Archaeological research at a rock festival was an important arena for meeting people who otherwise might never have come across archaeologists.